Recovery and characterisation of quinoa protein via neutral to alkaline extraction: protein profiles and heat-induced aggregation behaviour - Cui H; Roy D; Li S; Loo TS; Guo Q; Ye A (Elsevier B V, 2025)
This study investigated the impact of extraction pH (pH 7–11) on the yield, composition, protein profile and properties of quinoa protein isolate (QPI), including solubility, interfacial tension and heat-induced aggregation. Extraction pH considerably influenced protein yield, purity and solubility, with alkaline conditions promoting higher protein yield (from 27.4 % to 39.5 % as extraction pH increased from pH 7 to pH 11) but lower purity (from 89.7 % to 85.1 %) owing to the co-precipitation of carbohydrates. Sodium dodecyl sulphate–polyacrylamide gel electrophoresis analysis combined with liquid chromatography with tandem mass spectrometry revealed major protein profile in quinoa protein, confirming the abundance of 11S globulin. Moreover, extraction pH affected the solubility over a broad range of pH, interfacial properties and heat-induced aggregation behaviour of QPI. QPI extracted at pH 9 exhibited better solubility and better interfacial tension reduction capability but lower heat stability compared with QPI extracted at pH 11. Results from this study provided useful information and essential insights into the utilisation of quinoa proteins in various food applications.
Keywords: Aggregation; Alkaline extraction; Functionality; Protein composition; Quinoa protein